The Effect of Religious-Spiritual Education and Care on the Life Quality of Iranian Elderly A Systematic Review and Meta-Analysis - Faraji, Azam; Khalily, Mojgan; Naghibzadeh, Zahra Al-sadat; Kazeminia, Farahnaz; Kazeminia, Mohsen (2023)
Aging causes the reduction in physical and physiological strength and an increase in the odds of affliction with chronic physical and mental diseases ultimately affecting the quality of life (QoL). So far, several primary studies have been conducted on the impact of religious-spiritual education and care on the QoL of the elderly. However, to the best of our knowledge, a study that compiles and represents these findings in a published paper is lacking. Therefore, the current study conducted a systematic review and meta-analysis to investigate the effect of religious-spiritual education and care on the QoL of the elderly population. To access studies related to the aim of the study, SID, MagIran, IranMedex, IranDoc, Embase, PubMed, Scopus, Web of Science, and Google Scholar databases were searched. The search was done using relevant and validated keywords with MeSH/Emtree without time limitations until December 2021. The qualitative appraisal of the papers was done using the JBI checklist. To estimate the heterogeneity of studies, I2 index was used, and to combine the data and carry out a meta-analysis, Random Effects model was used. In the primary research, 1065 studies were found. The omission of the redundant cases led to a total number of 12 papers with a sample size of 317 in the intervention group and 321 in the control to be included in the meta-analysis. After the intervention, the mean score of QoL showed a significant increase by 1.42 ± 0.31 with a Confidence Interval of 95% (P<0.001). Meta-regression results showed that the increase in the year of conducting the study, and the number of intervention sessions, that the standardized mean difference had a decreasing trend, and that with the increase in the average age of the elderly, there was a rising trend (P<0.001). Therefore, it seems that the application of religious-spiritual education and care could be part of a program to improve the QoL of the elderly.
Keywords: Iran; Meta-analysis; Quality of life; Spirituality; systematic review